The Javelin and a Life (Nóema, 2021)
An ecosystem is like Kantian totality: it cannot be reduced to object of knowledge, since each element of it is internal to the contingent correlation which sustains it. Its accidental metamorphoses create worlds of sense which are infinitely on the way.
Keywords: totality; correlation; systemic globality; figures of truth; discourse